Autonomous learning model in online English classes: The benefits and challenges - Siti Maulia Rizki; Siti Sarah Fitriani; Sofyan A. Gani; Iskandar Abdul Samad (UNIB Press, 2023)
The post-pandemic phase has provided choices in the teaching and learning process, whether offline, online, or hybrid. Autonomous learning has become one of the preferred learning models dealing with online learning. This model of learning is believed to enhance students’ proficiency in EFL learning and enable learners to direct their learning. This qualitative study aims to investigate the benefits and challenges of implementing an autonomous learning model post-COVID-19 outbreak to EFL learners. There were three teacher-participants from Sukma Bangsa and Modal Bangsa high schools in Aceh. The teachers participated in a semi-structured interview, and the data from the interview were transcribed and coded through thematic analysis using the Coding system. The data analysis results indicate three benefits of autonomous learning through online platforms: meeting human needs, creating motivated and reflected learners, and developing communicative competence in second/foreign language learners. Furthermore, the challenges of autonomous learning are related to teachers’ roles, students’ beliefs, and social perspectives on autonomous learning. Based on the result, Autonomous Learning Model could be a choice as a learning model for online learning.